sequencia = a b
|
alternativa = a|b
![Diagrama Sintático - Diagrama de Sintaxe Alternativa Diagrama Sintático - Diagrama de Sintaxe Alternativa](DiagramaSintaticoAlternativa.png) |
De0ate1b = [a] /* 0:1 */
De0ate1b = (a)? /* 0:1 */
![](LazyBNFExemploDe0Ate1b.png) |
De0ate1d = (a b)? /* 0:1 */
![](LazyBNFExemploDe0Ate1d.png) |
De0ateInf1 = a* /* 0:inf */
![](LazyBNFExemploDe0AteInf1.png) |
De0ateInf2 = {a} /* 0:inf */
![](LazyBNFExemploDe0AteInf2.png) |
De0ateInf3 = [a+] /* 0:inf */
![](LazyBNFExemploDe0AteInf3.png) |
De0ateInf4 = [(a b)+] /* 0:inf */
![](LazyBNFExemploDe0AteInf4.png) |
De1ateInf1 = a+ /* 1:inf */
![](LazyBNFExemploDe1AteInf1.png) |
De1ateInf2 = (a b)+ /* 1:inf */
![](LazyBNFExemploDe1AteInf2.png) |
ComSeparador1=a(";"a)*
ComSeparador1=a {";" a}
|
ComSeparador4 = seq {";" seq}
seq = a b /* CSep = a b {";" a b} não simplificou*/
![](LazyBNFExemploComSeparador4.png) ![](LazyBNFExemploComSeparadorSeq.png) |
|
|